A positively biased external anode for energy control of plasma ions: hollow cathode and magnetron sputtering discharge. (8th April 2021) - Hippler, Rainer; Cada, Martin; Hubicka, Zdenek
Abstract: The performance of a positively biased external ring anode in combination with a hollow cathode (HC) discharge or a magnetron sputtering (MS) discharge, both with a Ti cathode and with Ar as working gas, is investigated. Plasma and floating potential increase as function of anode voltage. Energy-resolved mass spectrometry reveals that the kinetic energy of argon and titanium ions is enhanced by a positive anode voltage allowing for an effective energy control of plasma ions.